Ammonia stress corrosion cracking acceleration test method
The accelerated ammonia SCC test method promotes oxide film cracking through controlled polarization and composition in liquid ammonia, enabling precise and rapid evaluation of SCC susceptibility in metal materials.
Patent Information
- Application Number
- JP2023098069
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2043-06-14
AI Technical Summary
Existing ammonia stress corrosion cracking (SCC) evaluation methods in liquid ammonia environments are inaccurate and time-consuming, particularly when non-protective films form, suppressing pitting corrosion and making it difficult to assess susceptibility in materials with varying resistance to ammonia SCC.
An accelerated ammonia SCC test method involving anodic polarization of metal test pieces in liquid ammonia with controlled ammonium carbamate concentration and oxygen partial pressure, along with cathodic polarization to promote a thick and brittle oxide film formation, which is susceptible to cracking under stress, thereby evaluating SCC susceptibility in a short period.
The method accurately evaluates ammonia SCC susceptibility of metal materials in a short period, typically within 720 hours, compared to the usual one-year duration in actual tank environments, ensuring high accuracy and suitability for materials used in liquid ammonia transportation and storage.
Smart Images

Figure 2024179321000001 
Figure 2024179321000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for accelerated ammonia stress corrosion cracking testing of metal materials such as tanks used in a liquid ammonia environment. [Background technology]
[0002] In recent years, liquid ammonia has been attracting attention as a clean energy source because it does not emit CO2 when burned, and large-scale demand is expected. This has led to a demand for larger facilities to transport and store liquid ammonia. In general, when making tanks larger, thinner steel is used in order to reduce weight and construction costs, and therefore the use of high-strength steel is desirable.
[0003] On the other hand, in a liquid ammonia environment, there is concern that carbon steel may suffer from stress corrosion cracking due to liquid ammonia (hereinafter referred to as ammonia SCC). Therefore, for carbon steel structures that handle liquid ammonia, such as piping, storage tanks, tank cars, and line pipes, steel materials with low ammonia SCC susceptibility have been used and operational measures have been taken to suppress ammonia SCC.
[0004] SCC is a phenomenon that leads to destruction due to the superposition of corrosion reactions and stress, and occurs when material factors, environmental factors, and stress factors meet certain conditions. For example, ammonia SCC is known to correlate with the strength and hardness of a material. In other words, it is known that the higher the strength and hardness, the more ammonia SCC occurs, and when using carbon steel, it is considered desirable to use materials with a tensile strength of less than 600 MPa.
[0005] Therefore, when applying new materials that combine high strength with excellent ammonia SCC resistance, it is necessary to accurately evaluate the ammonia SCC susceptibility.However, since evaluating ammonia SCC susceptibility through exposure tests in actual liquid ammonia tanks requires long-term testing, an accelerated test that can evaluate the ammonia SCC susceptibility of steel materials in a short period of time is desired.
[0006] Such accelerated tests using liquid ammonia are disclosed in Patent Document 1 and Non-Patent Document 1. Patent Document 1 and Non-Patent Document 1 describe a test method in which a test steel piece is anodically polarized in liquid ammonia containing O2 and saturated CO2 at a gas pressure of 0.3 to 2.0 atm, thereby accelerating the dissolution of iron and evaluating ammonia SCC susceptibility in a short period of time. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 60-10575 [Non-patent literature]
[0008] [Non-Patent Document 1] Yoichi Nakai, "Development of an accelerated test method for stress corrosion cracking in liquid ammonia", Iron and Steel, Vol. 67, No. 14, 1981, pp. 2226-2233 Summary of the Invention [Problem to be solved by the invention]
[0009] In the environment where there is an excess of O2 described in Patent Document 1 and Non-Patent Document 1, a non-protective film is formed, resulting in a corrosion form close to general corrosion, which inhibits the growth of pitting corrosion (localized corrosion) that is the starting point of ammonia SCC, making it difficult to say that ammonia SCC susceptibility is accurately evaluated. In addition, since the growth of pitting corrosion (localized corrosion) is not promoted, it may not be possible to evaluate ammonia SCC susceptibility in materials that are not highly susceptible to ammonia SCC.
[0010] The present invention aims to solve the above problems and provide an accelerated ammonia SCC test method that can evaluate the ammonia SCC susceptibility of metal materials used in tanks for transporting and storing liquid ammonia with high accuracy and in a short period of time. [Means for solving the problem]
[0011] In order to achieve the above object, the present inventors conducted a detailed study on the ammonia SCC mechanism of steel sheet in liquid ammonia and obtained the following findings.
[0012] In a liquid ammonia environment, the following corrosion reactions occur on steel plates: Anode reaction: Fe → Fe 2+ +2e - Cathode reaction: O2 + 2NH4 + +4e - →2OH - +2NH3
[0013] As a result of the above corrosion reaction, an inactive oxide film is formed on the steel sheet surface. When cracks occur in this oxide film due to external stress, the dissolution of the exposed steel base is accelerated, causing pitting corrosion. The pitting corrosion becomes a stress concentration area, and film destruction and corrosion reactions progress at the tip of the pit, eventually leading to fracture. Therefore, it was thought that in order to promote the occurrence of pitting corrosion, which is the starting point of ammonia SCC, the oxide film formed on the steel sheet surface is prone to cracking due to external or residual stress.
[0014] They also discovered that by controlling the amount of O2 in liquid ammonia, a thick and brittle oxide film was formed on the surface of the steel sheet, making it possible to evaluate ammonia SCC susceptibility in a short period of time.
[0015] The present invention has been made based on the above findings, and the gist of the present invention is as follows.
[0016] [1] An accelerated ammonia stress corrosion cracking test method, characterized in that a metal test piece to which an external stress has been applied or which has residual stress is immersed in liquid ammonia containing 0.01 mass% or more ammonium carbamate and a gas partial pressure of 0.002 to 0.200 bar O2, and polarized to more than +1.0 V relative to the corrosion potential.
[0017] [2] The accelerated ammonia stress corrosion cracking test method according to [1], wherein the surface of the metal test piece immersed in the liquid ammonia is cathodically polarized and then polarized to a corrosion potential of more than +1.0 V.
[0018] [3] The accelerated ammonia stress corrosion cracking test method according to [1] or [2], wherein the liquid ammonia is stirred during the test. Effect of the Invention
[0019] According to the accelerated ammonia stress corrosion cracking test method of the present invention, it is possible to evaluate the ammonia SCC susceptibility of metal materials applied to tanks and the like used in a liquid ammonia environment with good accuracy and in a short period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as the present embodiment) will be described in detail. The present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the present invention. In the embodiment of the present invention, A (numerical value) to B (numerical value) means A or more and B or less.
[0021] [Polarized to more than +1.0 V relative to the corrosion potential] In the test method of the present invention, a metal test piece to which an external stress has been applied or which has residual stress is immersed in liquid ammonia containing 0.01 mass% or more of ammonium carbamate and O2 at a gas partial pressure of 0.002 to 0.200 bar, and is polarized to more than +1.0 V relative to the corrosion potential.
[0022] By polarizing the metal test piece to more than +1.0 V with respect to the corrosion potential, the anodic reaction is promoted on the surface of the metal test piece immersed in liquid ammonia, and a thick and brittle oxide film is formed on the surface of the test piece. On the surface of a metal test piece to which external stress has been applied or which has residual stress, the stress causes cracks in the oxide film, which promotes the occurrence of pitting corrosion due to local corrosion, and the ammonia SCC susceptibility can be evaluated in a short period of time. On the other hand, if the metal test piece is polarized to +1.0 V or less with respect to the corrosion potential, a thick and brittle oxide film is not formed, and such an effect cannot be obtained. Therefore, it is specified that the metal test piece is polarized to more than +1.0 V with respect to the corrosion potential. The metal test piece is polarized to preferably +1.3 V or more, more preferably +1.5 V or more with respect to the corrosion potential.
[0023] In addition, if the metal test piece is anodically polarized to a potential of more than +3.0 V relative to the corrosion potential, excessive nitrogen is generated by the reduction of NH3, and the area is covered with nitrogen bubbles, and the anode reaction does not occur in that area, so that the ammonia SCC susceptibility may not be evaluated. Therefore, the electrode range to be polarized is preferably +3.0 V or less relative to the corrosion potential, more preferably +2.7 V or less, and even more preferably +2.5 V or less.
[0024] The corrosion potential is the potential measured by immersing a metal test piece for evaluating ammonia SCC susceptibility, or a metal test piece taken from the same metal material as the evaluation target metal material, in liquid ammonia for 5 minutes or more while applying external stress or with residual stress. There is no particular limitation on the method for measuring the potential, but it can be measured by the two-electrode method or the three-electrode method.
[0025] The polarization (application of electric potential) and the measurement of the corrosion potential of the metal test piece can be performed, for example, by using a potentiostat (a constant potential electrolysis device) with the metal test piece as the working electrode (sample electrode). In this case, it is preferable to use platinum electrodes, which are stable in liquid ammonia, as the counter electrode and the reference electrode.
[0026] <Test solution> In the test method of the present invention, liquid ammonia containing 0.01 mass % or more of ammonium carbamate and O2 at a gas partial pressure of 0.002 to 0.200 bar is used as the test solution.
[0027] [Ammonium carbamate content: 0.01 mass% or more] Liquid ammonia normally contains trace amounts of CO2 as an impurity, and in liquid ammonia, CO2 dissociates and reaches an equilibrium state as shown in the following reaction formula. 2NH3+CO2⇔NH4CO2NH2⇔NH4 + +NH2CO2 -
[0028] Although the electrical conductivity of liquid ammonia without impurities is small, when ammonium carbamate (NH4CO2NH2) is contained, the electrical conductivity of liquid ammonia increases due to the dissociation reaction, and the corrosion reaction is accelerated. If the ammonium carbamate content in liquid ammonia is less than 0.01 mass%, such an effect cannot be obtained, and it is difficult to accelerate ammonia SCC by polarizing the metal test piece. Therefore, the ammonium carbamate content in liquid ammonia is specified to be 0.01 mass% or more. It is preferably 0.03 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.30 mass% or more.
[0029] The upper limit of the content of ammonium carbamate in the liquid ammonia is not particularly limited, and may be up to the saturated amount, for example, 6.00 mass% or less, 1.00 mass% or less, or 0.50 mass% or less.
[0030] The method of adding ammonium carbamate to liquid ammonia is not particularly limited, but it is preferable to place a predetermined amount of ammonium carbamate in the test vessel before introducing liquid ammonia. The placement of the ammonium carbamate can be replaced by blowing in an amount of CO2 gas or placing solid CO2 (dry ice) that will give the predetermined amount of ammonium carbamate content.
[0031] [O2 content: gas partial pressure 0.002~0.200bar] Since O2 has the effect of forming an oxide film in liquid ammonia, the presence of O2 is essential for evaluating ammonia SCC susceptibility. If the O2 content in liquid ammonia is less than 0.002 bar in gas partial pressure, this effect is not obtained, making ammonia SCC evaluation difficult. It is preferably 0.010 bar or more, more preferably 0.050 bar or more. On the other hand, if the O2 content in liquid ammonia exceeds 0.200 bar in gas partial pressure, an oxide film with no protective properties is formed, resulting in a corrosion form close to general corrosion, which inhibits the occurrence and growth of pitting corrosion (localized corrosion), making ammonia SCC evaluation difficult. Therefore, the O2 content in liquid ammonia is specified to be 0.002 to 0.200 bar in gas partial pressure. It is preferably 0.175 bar or less, and more preferably 0.150 bar or less.
[0032] Although the method of adding O2 to liquid ammonia is not particularly limited, from the viewpoint of a stable supply of O2, it is preferable to blow a predetermined amount of O2 gas into the test vessel before introducing liquid ammonia. The blowing of the O2 gas can be replaced with blowing of an amount of air gas that can obtain the predetermined amount of O2 gas partial pressure.
[0033] [Liquid ammonia] The purity of the liquid ammonia used in the test solution is not particularly limited, but if it contains HO and oil, stress corrosion cracking of the metal test piece is more likely to be suppressed. Therefore, it is preferable that the amount of HO and oil contained as impurities in the liquid ammonia is less than 0.05 mass% each.
[0034] [Cathode polarization] A passive film may be formed on the surface of the metal test piece before immersion in liquid ammonia. After immersion in liquid ammonia, cathodic polarization is performed prior to anodic polarization to remove the passive film on the surface of the metal test piece, homogenizing the initial surface state and enabling a more accurate ammonia SCC susceptibility evaluation. The conditions for cathodic polarization are not particularly limited, but it is preferable to perform the cathodic polarization at -1.0V or less and -3.0V or more with respect to the corrosion potential for 5 minutes to 30 minutes.
[0035] [Liquid ammonia stirred during testing] The corrosion reaction is affected by the solution composition of the liquid ammonia on the surface of the metal test piece. By stirring the liquid ammonia containing ammonium carbamate and O2, which is the test solution, the solution composition on the surface of the immersed metal test piece can be made uniform, allowing for a more accurate ammonia SCC susceptibility evaluation. Furthermore, since stirring promotes the supply of ions to the metal test piece surface, the time required for ammonia SCC susceptibility evaluation can be shortened. Therefore, it is preferable to stir the liquid ammonia containing ammonium carbamate and O2 during the test. Since ammonia SCC susceptibility is affected by nitrogen, carbon dioxide, oxygen, etc., it is preferable to use a stirrer for stirring. In order to stabilize the supply of ions to the metal test piece surface, it is preferable to stir continuously at 10 rpm or more.
[0036] <Metal test piece> The test method of the present invention is a method for promoting ammonia SCC by applying an electric potential, and therefore can be applied to conductive metal materials. The metal materials are not particularly limited in terms of their component composition or metal structure. Specific examples of the metal materials include those containing metal elements (e.g., Fe, Cu, Al, Ni, Ti, etc.) as the main component (i.e., 50 mass% or more), such as steel (iron alloy), copper alloy, aluminum alloy, nickel alloy, titanium alloy, etc. In particular, since these materials are generally used in structures exposed to a liquid ammonia environment and resistance to ammonia SCC is important, it is preferable to apply the test method to steel materials.
[0037] When a steel material is used as the metal test piece, the carbon equivalent and hardness of the steel material are not particularly limited. It is generally known that the higher the carbon equivalent and hardness of a steel material, the higher the ammonia SCC susceptibility, and it is preferable that the steel test piece has a carbon equivalent of 0.05% or more and a Vickers hardness of 100 Hv or more. The metal test piece used in the test method of the present invention may be one taken from a metal material whose ammonia SCC susceptibility is to be evaluated, or one taken from a metal material having the same or similar component composition and metal structure as the said metal material.
[0038] The shape and size of the metal test piece are not particularly limited and may be appropriately determined depending on the test cell and the method of applying external stress to be used or may be selected from known standards. However, the exposed area (cm2) of the metal test piece may be adjusted so as to reduce the effect of the corrosion reaction on the solution composition. 2 The specific liquid volume, which is the amount of liquid ammonia solution (mL) relative to the 2 The upper limit of the specific liquid volume is not particularly limited, but if the specific liquid volume is excessively large, the cost of the test equipment etc. will increase, so it is preferable that the upper limit is 500 mL / cm 2 It is preferable that:
[0039] [External stress / residual stress] Since the test method of the present invention is an accelerated ammonia stress corrosion cracking test, a metal test piece to which an external stress has been applied or which has a residual stress is immersed in a test solution. The method of applying the external stress or the residual stress is not particularly limited, but for example, an external stress can be applied by a known method such as four-point bending, U-bending, or a constant load method, and a residual stress can be applied by carrying out a heat treatment, welding, processing, or the like.
[0040] The magnitude of the applied external stress or residual stress may be appropriately set depending on the test purpose (for example, the intended use of the material to be evaluated), but from the viewpoint of causing cracks in the thick and brittle oxide film formed on the surface to induce local pitting corrosion, it is preferable to apply a load of 100% or more of the yield strength YS (MPa) of each metal test piece, and more preferably a load of 120% or more. Since an increase in the applied external stress or residual stress can promote ammonia SCC, there is no particular upper limit as long as the metal test piece itself is not damaged, such as cracked.
[0041] <Other test conditions> The test temperature (temperature of the test solution) at which the test method of the present invention is carried out can be appropriately selected depending on the purpose of the test, but since the corrosion reaction is suppressed at low temperatures and the test period tends to be long, it is preferably set to 0 to 60° C. In order to further improve the test accuracy, it is preferable to keep the error between the set test temperature and the actual test temperature within ±5° C.
[0042] The test period for carrying out the test method of the present invention is not particularly limited and can be set appropriately depending on the intended use of the metallic material to be evaluated, but in order to apply a new material, the shorter the test period, the better, and it is preferably within 720 hours. Since an ammonia SCC test under an actual tank environment (actual liquid ammonia) generally requires a test period of about one year, the use of the test method of the present invention can shorten the test period to about 1 / 10 or less.
[0043] The test conditions other than those mentioned above are not particularly limited, and may be appropriately selected from known conditions used in corrosion tests. Test equipment, test cells, and the like may be those known in the art, such as those described in Patent Document 1 and Non-Patent Document 1. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.
[0045] [Ammonia SCC test in actual tank environment] As a preliminary study to confirm the effectiveness of the test method of the present invention, five types of steel (steel types A to E) with different composition were used as test steels, and an ammonia SCC test was performed in an actual tank environment using actual liquid ammonia to evaluate the ammonia SCC susceptibility.
[0046] Table 1 shows the carbon equivalent (CE), yield strength (YS) and Vickers hardness (HV0.5) of the steel materials subjected to the ammonia SCC test.
[0047] The carbon equivalent (CE) was calculated from the composition of the test steel material using the following formula. CE=C+Mn / 6+Si / 24+Ni / 40+Cr / 5+Mo / 4+V / 14 (In the formula, the element symbols indicate the content (mass%) of each element in the test steel material.)
[0048] The yield strength and Vickers hardness were measured at the 1 / 4 position of the plate thickness in accordance with JIS Z 2241 and JIS Z 2244. The Vickers hardness was measured at 20 points using a Vickers test with a load of 500 g, and the average value was calculated.
[0049] Test pieces measuring 5 mm thick x 15 mm wide x 115 mm long were taken from the 1 / 4 plate thickness position of test steels A to E. The taken test pieces were ultrasonically degreased in acetone for 5 minutes, and then an external stress (100% YS) equal to the yield strength of each test piece was applied by four-point bending. The four-point bent test pieces were immersed in a real liquid ammonia tank and removed after one year. After removing the corrosion products from the surface of the removed test pieces, the surface and cross section of the test pieces were visually observed for cracks and evaluated for the presence or absence of cracks.
[0050] Those that had cracks were judged as having SCC (good), and those that did not have cracks were judged as having no SCC (bad). The judgment results are also shown in Table 1 as the occurrence of SCC in actual liquid ammonia tanks.
[0051] [Table 1]
[0052] As can be seen from Table 1, in an actual liquid ammonia tank, no SCC occurred in steels A and B. On the other hand, SCC occurred in steels C to E.
[0053] [Ammonia SCC accelerated test] The ammonia SCC acceleration test of the present invention was carried out on the test steels A to E for which the ammonia SCC occurrence state in an actual tank environment was examined as described above, and the ammonia SCC susceptibility was evaluated.
[0054] Table 2 shows the test conditions for the ammonia SCC accelerated test. Test pieces measuring 5 mm thick x 15 mm wide x 115 mm long were taken from the 1 / 4 position of the plate thickness of test steels A to E, and ultrasonically degreased in acetone for 5 minutes. An external stress of 1.2 times the yield strength of each test piece (120% YS) was applied by four-point bending. Ammonium carbamate and O2 were introduced into the 2 L test cell containing the four-point bending test pieces in the amounts shown in Table 2, and then liquid ammonia was filled in. The specific liquid volume was 42 mL / cm. 2 After that, the corrosion potential of the test piece was measured by a potentiostat, and the test was started by controlling the corrosion potential after 1 hour to a predetermined potential. After 168 to 2160 hours of immersion, the test piece was taken out of the test cell, the corrosion products on the surface of the test piece were removed, and the surface and cross section were visually observed for cracks to evaluate the presence or absence of cracks.
[0055] The immersion test used liquid ammonia with a purity of 99.999% or more. The measurement of potential using a potentiostat and the application of potential were performed using the three-electrode method, with platinum electrodes used as the reference electrode and counter electrode. The test temperature was set at 25°C. Stirring during the test was performed continuously at 10 rpm using a stirrer placed in the test cell.
[0056] The occurrence of SCC was evaluated by conducting the immersion test 10 times for each test number, and if one or more cracks occurred throughout the test, it was judged as "Good" for SCC occurrence, and if no cracks occurred, it was judged as "No SCC" for no SCC. For the results of "Good" for SCC occurrence, the probability of SCC occurrence was calculated. For the results of "No SCC" for no SCC, the probability of occurrence was recorded as 0%.
[0057] For tests that showed no SCC (x), those in which the SCC occurrence was the same as that in the actual liquid ammonia tank for the same steel type shown in Table 1 (x), were judged to have good evaluation accuracy. For tests that showed SCC occurrence (o), those in which the SCC occurrence was the same as that in the actual liquid ammonia tank for the same steel type shown in Table 1 and the occurrence probability was 70% or more were judged to have good evaluation accuracy. The occurrence probability is expressed as the number of tests in which SCC occurrence was confirmed out of 10 immersion tests, expressed as a percentage. In addition, for tests in which the evaluation accuracy was judged to be good, those in which the test period was 720 hours or less were judged to have good evaluation periods. Tests other than those judged to be good for evaluation accuracy and evaluation period were judged to be poor. Table 2 shows the accelerated test results including the SCC occurrence status, occurrence probability, evaluation accuracy, and evaluation period.
[0058] [Table 2]
[0059] As can be seen from Table 2, in the examples of the present invention, the SCC susceptibility could be evaluated within 720 hours to the same level as in the environment simulating an actual liquid ammonia tank. On the other hand, in the comparative examples, the evaluation accuracy was "poor" or the evaluation period was "poor", and the ammonia SCC susceptibility could not be evaluated with good accuracy and in a short period of time. [Industrial Applicability]
[0060] According to the present invention, it is possible to provide an accelerated ammonia stress corrosion cracking test method capable of evaluating the ammonia stress corrosion cracking susceptibility of a metallic material with good accuracy and in a short period of time. Moreover, by using the test method of the present invention, it becomes possible to evaluate the ammonia stress corrosion cracking susceptibility of a metallic material with high accuracy and in a short period of time. The test method of the present invention is very useful for evaluating the ammonia stress corrosion cracking susceptibility of a metallic material, and can be advantageously used for the selection and development of metallic materials having excellent ammonia stress corrosion cracking resistance that can be suitably used for structures for transporting or storing liquid ammonia.
Claims
1. Metal test pieces to which external stress has been applied or which have residual stress are subjected to a gas partial pressure of 0.002 to 0.200 bar containing 0.01 mass% or more ammonium carbamate. 2 and polarizing the specimen to a corrosion potential of more than +1.0 V in liquid ammonia containing the compound.
2. 2. The ammonia stress corrosion cracking accelerated test method according to claim 1, wherein the surface of the metal test piece immersed in the liquid ammonia is polarized to a corrosion potential of more than +1.0 V after cathodic polarization.
3. 3. The method for accelerated ammonia stress corrosion cracking testing according to claim 1, wherein the liquid ammonia is stirred during the test.
Citation Information
Patent Citations
Low hydrogen type coated electrode
JP1982137096A
Corrosion environment sensor and corrosion environment controller
JP1993340858A
Crack growth test apparatus
JP2001153789A
Method and apparatus for manufacturing stress corrosion crack test specimen
JP2006010427A
Steel material
JP2019094563A
Cited By
Disk device
CN121862168A
